What drives the VIPs of the art world? Collectors in the light of textual analysis (2015)
While cultural consumption has been the object of several studies in economics, the behavior of art collectors has seldom been investigated. This paper aims to fill this gap by empirically profiling art collectors in terms of their motivations and the experiences that affect their purchase choices. After discussing the theoretical framework of con-sumption theory and its evolution applied to art collectors, we apply textual analysis to 115 interviews of international collectors published in the French business magazine Les Echos. Our main findings allow us to distinguish three main groups of col-lectors (two of contemporary art, and one of Old Masters and ancient art), each of which is characterized by distinctive fea-tures in terms of motivations and experiences. In particular, we identify three kinds of relational experience, based respectively on shared experience, personalized relation and participation.